Modification of Hayami value-added analysis calculations in the processing of cayenne pepper - Padapi, Astrini; R., Fitriani; Wulandary, Ayu; Haryono, Iranita (Agribusiness Department, Agriculture and Forestry Faculty, Universitas Sulawesi Barat, Indonesia, 2023)
The problem in this research is the durability of the chili harvested and the fluctuations in the price of chili that are not certain. This opportunity to improve the standard of living did not last long because many chilies from other regions flooded the surrounding markets and were more in demand by consumers because they were cheaper. This situation is very worrying because it impacts the decline in selling power so that there is a buildup of harvests and spoilage of chilies. The above problems must be the attention of all parties to find the best solution so that farmers can take advantage of opportunities. Efforts taken to extend the shelf life of chili are applying chili processing technology to food products, such as chili shreds. This research aims to assist farmers in increasing their income and getting solutions to their business problems audience for other researchers. Analysis of the data used in this study is the analysis of added value (Added Value). The Hayami method is carried out in two stages, the first stage is calculating output, input and price, and then the second stage is calculating revenue and advantage. In this study, the Hayami method was used, adapted to the modification, which was the basis of calculation using the value of money. The management of fresh cayenne pepper commodities to shredded cayenne pepper is feasible to run. The added value of shredded cayenne pepper products is Rp 145,000/kg with every Rp 1, the product’s value contains an added value of Rp 145. It proves that the use of fresh cayenne pepper into shredded cayenne pepper is a profitable business and can help reduce damage to easily damaged chilies. If not sold immediately.